Selfie Jilbab : Produksi Identitas Virtual Perempuan di Instagram - Kurniawati, Juliana; Yuliani, Fitria; Safitra, Linda (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Selfie jilbabs are an interesting selfie style to study because jilbabed women often seem to have no freedom in producing virtual identities. Some religious norms are considered to limit self-representation in cyberspace. This article aims to examine the production of virtual identity formed by women wearing headscarves through selfies on compilation accounts on Instagram. Theo van Leeuwen's social semiotics and Michel Foucault's concept of technology of the self are used to examine uploads of selfie jilbabs on the compilation accounts @jilbab_chantik, @selfie_mukena and @jilbab_sweet. The third account of this compilation was chosen because it represents three representations of selfie style. Instagram is a space that offers freedom for women who wear hijab to express themselves through photos. However, when the photo is submitted to the admin compilation account for editing, a modification of the authority for the photo occurs. A study of three photo compilation accounts shows three dominant virtual identities generated by admins, namely beautiful women, sexy women, and pious women. Viewers confirmed these three identities by liking and actively commenting on photos uploaded to the Instagram newsfeed.